2017
DOI: 10.1016/j.rboe.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Blood level changes in total knee arthroplasty with and without a tourniquet

Abstract: ObjectiveTo evaluate the difference between the total blood loss in patients undergoing primary total knee arthroplasty with and without the use of tourniquet.MethodsA retrospective cohort study, with analysis of medical records of patients undergoing primary total knee arthroplasty in 2015, with and without the use of a tourniquet. Comparison was performed of hemoglobin (HB) and hematocrit (HT) variation in the complete blood count (CBC) during the pre- and post-operative period between the two groups.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
1
2
0
8
Order By: Relevance
“…This finding is consistent with prior literature demonstrating the effectiveness of tourniquet use in reducing intraoperative blood loss [18,19,51]. The true relationship between tourniquet use and transfusion rates in TKA has been a topic of much debate with numerous conflicting results [18,20,[52][53][54]. Our study showed no significant difference in transfusion rates between TA and TU groups, consistent with the findings of Wang et al [54] and Zhang et al [16].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with prior literature demonstrating the effectiveness of tourniquet use in reducing intraoperative blood loss [18,19,51]. The true relationship between tourniquet use and transfusion rates in TKA has been a topic of much debate with numerous conflicting results [18,20,[52][53][54]. Our study showed no significant difference in transfusion rates between TA and TU groups, consistent with the findings of Wang et al [54] and Zhang et al [16].…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies have evaluated the influence of tourniquet use during TKA on blood loss and transfusion, no consensus has been reached about whether or not to use a tourniquet in routine primary TKA because of the diversity of current literature results [ 17 ]. A retrospective cohort study of 117 patients by Barros et al [ 18 ] showed that tourniquet use in TKA resulted in a lower decrease in hemoglobin and hematocrit as well as fewer necessary blood transfusions. Surprisingly, Schnettler et al [ 19 ] reported that tourniquet application during TKA resulted in a paradoxical increase in blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there was a signi cant negative correlation between the length of tourniquet use and postoperative complications. The latest opinion on whether to use tourniquet in total knee arthroplasty: By comparing the postoperative rehabilitation of patients in the group with and without tourniquet, it has been found that the non-use of tourniquet in total knee arthroplasty can reduce the postoperative pain and limb swelling, without increasing the risk of postoperative complications, and without affecting the quality of prosthesis installation and xation [21,22]. It has been suggested that long-term use of tourniquet can reduce intraoperative and intraoperative total blood loss, while short-term use of tourniquet can reduce postoperative and postoperative hidden blood loss without increasing the rate of allogeneic blood transfusion [23].…”
Section: Discussionmentioning
confidence: 99%